Title IX and the evolution of high school sports - Betsey Stevenson (Center for Economic Studies and ifo Institute (CESifo), 2007)
The passage of Title IX, the 1972 Education Amendments to the Civil Rights Act, expanded high school athletic opportunities to include girls, revolutionizing mass sports participation in the United States. This paper analyzes high school athletic participation in the United States and how sports offerings for boys and girls changed subsequent to the passage of this legislation. Girls' sports participation rose dramatically both following the enactment of Title IX and subsequent to enhancements to its enforcement. Approximately half of all girls currently participate in sports during high school; however, there remains a substantial gap between girls and boys participation in many states. States' average education level and social attitudes regarding Title IX and women's rights are correlated with this remaining gender gap. Examining individual high school students, sports participation is seen more frequently among those with a privileged background: white students with married, wealthy, educated parents are more likely to play sports. This finding points to an overlooked fact - while Title IX benefited girls by increasing the opportunity to play sports, these benefits were disproportionately reaped by those at the top of the income distribution.
Keywords: J16; J18; J24; I2; 330; Sport; Allgemeinbildende Schule; Männer; Frauen; Reform; Bürgerliches Recht; Geschlechterdiskriminierung; Schätzung; USA